Membangun Identitas Multikultural : Analisis Strategi Komunikasi Pemerintah Kota Semarang dalam Kegiatan Dugderan 2025 - Rachma, Hanna Sabrina (Universitas Muhammadiyah Magelang, 2025)
Semarang City is the capital city of Central Java whose people have diversity in terms of ethnicity and religion. This makes Semarang City have a tradition that is a cultural discovery point, namely Dugderan, by combining the 3 ethnicities (Javanese, Arab, and Chinese). The government through the Department of Culture and Tourism is taking advantage of this momentum to explore the uniqueness of culture in order to form an identity for Semarang City along with promoting the creative economy so that the community is involved in the Dugderan activity process. The purpose of this study is to determine the communication strategy implemented by the Semarang City government in building a multicultural identity through the Dugderan tradition. This study uses a qualitative research method using a qualitative descriptive approach. This study uses the theory of Strategic Communication. Primary data was obtained from the process of direct observation and interviews with parties related to this study, namely the organizers of the Dugderan event and owners of Micro, Small, and Medium Enterprises (MSMEs). Meanwhile, secondary data was obtained through searching research journals, books, the internet and documentation containing images or photos related to the research subject. The results of this study conclude that the communication strategy implemented by the government has succeeded in creating a tradition that supports tolerance and diversity in Semarang City. Thus, Dugderan not only functions as a cultural event, but also as a platform to strengthen the multicultural identity of the Semarang society.